2021
DOI: 10.1002/macp.202100010
|View full text |Cite
|
Sign up to set email alerts
|

What Does Conversion Mean in Polymer Science?

Abstract: The definition of the term "conversion" is discussed for a variety of polymer syntheses. It is demonstrated that in contrast to organic and inorganic chemistry several different definitions are needed in polymer science. The influence of increasing conversion on structure and topology of homo-and copolymers is illustrated. Chain-growth polymerizations, such as radical polymerization or living anionic polymerizations of vinyl monomers, condensative chain polymerization, two and three-dimensional step-growth pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Over the past 15 years research on synthesis and characterization of cyclic polymers, in general, [ 36 ] and cPLA in particular [ 37–56 ] has found increasing interest. Cyclic polymers have a higher coil density than their linear counterparts with the consequence of lower melt and solution viscosities which may be advantageous for processing of high molar mass polymers from the melt.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 15 years research on synthesis and characterization of cyclic polymers, in general, [ 36 ] and cPLA in particular [ 37–56 ] has found increasing interest. Cyclic polymers have a higher coil density than their linear counterparts with the consequence of lower melt and solution viscosities which may be advantageous for processing of high molar mass polymers from the melt.…”
Section: Introductionmentioning
confidence: 99%
“…About 20 years later the author found that cyclic tin compounds derived from dimercaptanes or diphenols (Scheme 2) initiate a REP which involves elimination pf the catalyst, so that cyclic polyesters become the main reaction product (Scheme 3). 12–15 …”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and characterization of cPLA have rapidly increased over the past 15 years. [ 7–40 ] The polymerization methods may be subdivided into two categories, first, polymerizations obeying the ROPPOC definition, meaning ring‐opening polymerization with simultaneous polycondensation (including cyclization), [ 41 ] and second, ring‐expansion polymerization (REP) using covalent cyclic catalysts. [ 42 ] The present work is based on REPs catalyzed by two cyclic tin compounds, 2,2‐dibutyl‐2‐stanna‐1,3‐dithiolane (DSTL) and 2‐stanna‐1.3‐dioxa‐4,5,6,7‐dibenzazepine (SnBiph, see Scheme ), because these catalysts have proven in recent REPs conducted in bulk, that they may yield medium and high molecular weight cPLA with average number molecular weights ( M n ) up to 200 000 and average weight molecular weights ( Mw ) up to 400 000) along with extraordinarily high melting temperatures ( T m ) and melting enthalpies (Δ H m ).…”
Section: Introductionmentioning
confidence: 99%